Cerebrovascular atherosclerosis correlates with Alzheimer pathology in neurodegenerative dementias - Yarchoan, Mark; Xie, Sharon X.; Kling, Mitchel A.; Toledo, Jon B.; Wolk, David A.; Lee, Edward B.; Van Deerlin, Vivianna; Lee, Virginia M.-Y.; Trojanowski, John Q.; Arnold, Steven E. (Brain (London, England : 1878), 2012)
A growing body of evidence demonstrates an association between vascular risk factors and Alzheimer’s disease. This study investigated the frequency and severity of atherosclerotic plaques in the circle of Willis in Alzheimer’s disease and multiple other neurodegenerative diseases. Semi-quantitative data from gross and microscopic neuropathological examinations in 1000 cases were analysed, including 410 with a primary diagnosis of Alzheimer’s disease, 230 with synucleinopathies, 157 with TDP-43 proteinopathies, 144 with tauopathies and 59 with normal ageing. More than 77% of subjects with Alzheimer’s disease had grossly apparent circle of Willis atherosclerosis, a percentage that was significantly higher than normal (47%), or other neurodegenerative diseases (43–67%). Age- and sex-adjusted atherosclerosis ratings were highly correlated with neuritic plaque, paired helical filaments tau neurofibrillary tangle and cerebral amyloid angiopathy ratings in the whole sample and within individual groups. We found no associations between atherosclerosis ratings and α-synuclein or TDP-43 lesion ratings. The association between age-adjusted circle of Willis atherosclerosis and Alzheimer’s disease–type pathology was more robust for female subjects than male subjects. These results provide further confirmation and specificity that vascular disease and Alzheimer’s disease are interrelated and suggest that common aetiologic or reciprocally synergistic pathophysiological mechanisms promote both vascular pathology and plaque and tangle pathology.